Perception of public and private clients on the benefits of partnering with contractor in industrialised building system / Faridah Muhamad Halil …[et al.] - Muhamad Halil, Faridah; Romeli, Norsyakilah; Azman, Mohd Azrai; Hasim, Mohamad Sufian (Universiti Teknologi MARA, 2021)
Partnering is generally is a commitment by those involved in a project through working closely or cooperatively. It is a concept of the relationship practice between organisations. It usually was based on the reputation of good quality of work done in the industry. Not all Malaysian's construction industry clients exercise the partnering while selecting the contractor in the Industrialized Building System. Failure to exercise partnering will impact the project delay, cost overrun and defect of the product received. The methodology adopted used a qualitative approach. The sampling selected is purpose sampling. The public and private clients revealed the benefits of partnering in the industrialized building system: early completion, cost-saving, quality received, easy to solve a problem and a return on investment in the development projects.